Improving Financial Efficiency through Integrated Human Resource Management and the Mediating Role of Leadership and Organizational Culture in Organizational Performance - Asmini; Aditya Halim Perdana Kusuma Putra Putra; Andi Adawiah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study investigates the integration of Human Resource Management (HRM) practices and their impact on organizational financial efficiency, mediated by leadership and organizational culture. Engaging employees from diverse industries, the research utilizes purposive sampling with a minimum target of 200 participants. Primary data is collected through validated five-point Likert scale questionnaires and proceed with SMARTPLS to answer the hypotheses. Findings indicate that effective financial management practices contribute to enhancing organizational performance and serve as a foundational growth factor. Strong correlations are identified between financial management, organizational performance, leadership, organizational culture, and productivity. Investments in HRM practices influence critical aspects such as leadership, organizational culture, organizational performance, and productivity, fostering a productive work environment. Effective leadership shapes a culture aligned with organizational values, boosting team performance and productivity. The implications of these findings are vital in strategic decision-making, including resource allocation, HRM strategies, and leadership development. An integrated management approach combining financial and HRM aspects is crucial for optimizing organizational performance. Effective leadership development is key to enhancing organizational culture, performance, and productivity. Keywords: HRM Practices, Financial Management Practices, Financial Efficiency, Leadership, Organizational Culture, Productivity, Organizational Performance.